Near-infrared Spectra of a Sample of Galactic Unclassified B[e] Stars - Arias, Maria L. (2018)
Fil: Arias, Maria L. Departamento de Espectroscopía, Facultad de Ciencias Astronómicas y Geofísicas, Universidad Nacional de La Plata Paseo del Bosque S/N, La Plata, B1900FWA, Buenos Aires, Argentina. IALP (CCT La Plata—CONICET, UNLP) Paseo del Bosque S/N, La Plata, B1900FWA, Buenos Aires, Argentina.